KORELASI MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA SELAMA DARING - Oktina Khoirunnisa; Mona Chairani; Joice Ronitua Simamora (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2022)
Indonesia experienced the Covid-19 pandemic, precisely at the beginning of 2020. This pandemic had an impact on various sectors, one of which was the education sector. Students and college students still have to follow the policies of the government to implement Distance Learning (PJJ). Although it has been supported by various technologies during the PJJ, there are still gaps that cause learning to be less effective. One of the things that is feared is that if the PJJ lasts for a long time, it will result in learning loss or reduced motivation, knowledge and skills academically. Online learning is learning that uses the internet network supported by learning applications.